PENERAPAN PENGAMBILAN GAMBAR PADA VIDEO PROMOSI (SHORT) KEGIATAN UNIVERSITAS BINA DARMA PALEMBANG - Nurul Azizah; Dimas Umboro (Bajang Institute, 2025)
This study aims to analyze the application of camera techniques in promotional videos for activities at Universitas Bina Darma Palembang. Promotional videos are crucial in capturing the attention of prospective students and the public regarding various university activities. Proper camera techniques can make the video more engaging and help the audience better understand the message being conveyed. This research uses a qualitative method with a case study approach, involving direct observation of the promotional video production process and interviews with the production team. The main focus of this study is to explore how camera techniques, such as angle selection, lighting, and visual composition, are applied in promotional videos. The findings reveal that choosing the right angles, dynamic camera movements, and good lighting are essential in creating an appealing visual presentation and enhancing the promotional message. Therefore, the effective application of camera techniques can improve the quality of promotional videos and better support the goals of promoting university activities. This research is expected to provide valuable insights for developing promotional video production techniques in the educational field.